"Her scarf is a garbage bag wrapped around her head": Muslim youth experiences of Islamophobia in Sydney primary schools. (February 2023) - Mourad, Zainab
This qualitative study investigates the ways in which Muslim minority youth experience Islamophobia in south-west Sydney primary schools. Islamophobia has occupied the Australian discursive context since the September 11 attacks and the ensuing War on Terror in 2001, and was amplified in the recent decade following the rise of Daesh and events of home-grown terrorism. In schools, minority Muslim students in Australia have been considered a problem for some time. Since the early phases of migration in the 1970s, Muslims have been constructed as a pedagogical challenge. More recently, this has adopted political overtones, and concerns regarding educational attainment have moved towards issues of national security and socio-political integration. To understand the ways in which the wider discursive context filters to schools, the study is underpinned by critical theory, combined with a critical ethnographic case study methodology. Drawing on the voices of Muslim students aged 10–12 across three schools, the critical discourse analysis found that Islamophobia was experienced by Muslim students in primary schools drawing on visible and physical cultural markers of being Muslim including the Arabic language, the hijab and Islamic practices. This paper contends that Islamophobia should be formally recognised as a form of cultural racism in schools.